Türk-İslam sentezcilerinde din - Tepegöz, Ahmet Selim (My University, 2010)
slam Sentezi, Din, Din Sosyolojisi, Milliyetçilik ÖZET TÜRK-İSLAM SENTEZCİLERİNDE DİN Mensuplarına göre, Türklük ile İslam’ın bin yılı aşkın süredir ayrılmaz birlikteliği anlamına gelen Türk-İslam Sentezi, 1970’li yıllardan beri Türk siyasi ve fikir hayatındaki etkileriyle yoğun şekilde tartışılmaktadır. Türk-İslam Sentezcilerince; İslam, Türklük ve Türk milleti için vazgeçilemez bir hayat kaynağıdır. Zaten dinin, toplumsal hayat ve kurumlar üzerinde vazgeçilemez işlevleri ve etkileri bulunmaktadır. Bu işlev ve etkiler istisnasız tüm toplumlarda rahatlıkla müşahede edilebilmektedir. Dolayısıyla din ve milliyetçilik esasen birbirleriyle çatışan olgular değildirler. Bazı toplumların dini telakkileri bu gerçeğe aykırı sonuçlar ortaya çıkarmışsa da İslam’ın milliyetçilikle ve milli kimlikle hiçbir problemi yoktur. İslam’ın karşı çıktığı husus milliyetçilik değil ırkçılıktır ki, Türk milliyetçiliği de zaten ırkçılığa karşıdır. Name and Surname: Ahmet Selim Tepegöz Field: Theology Programme: Sociology of Religion Supervisor: Professor Yümni Sezen Degree Awarded and Date: Doctorate – October 2010 Turk-Islam Synthesis, Religion, Sociology of Religion, Nationalism

RELİGİON İN TURK-ISLAM SYNTHESİZERS According to its members, Turk-Islam synthesis meaning the inseparable integrity of Turkishness and Islam for more than 1000 years has been discussed intensively with its effects on Turkish political and intellectual life since 1970s. According to Turk-Islam Synthesizers, Islam is an indispensable source of life for Turkishness and Turkish nation. Religion already has indispensable functions and effects on social life and institutions. These functions and effects can be observed easily in all societies without exception. Therefore, religion and nationalism are not basically the cases which collide with one another. Although the religious viewpoints of some societies have revealed the results contrary to this fact, Islam doesn’t have any problems with nationalism and national identity. What Islam protests against is racism not nationalism since Turkish nationalism is in any case against racism.
Keywords: Din; Din Sosyolojisi; İslam Dini